Childrens and parents: The Perception of Parent Inventory - Merino-Soto, César (2003)
The present study explores the psychometric properties of the Parent Perception Inventory (Hazzard et al., 1983), instrument elaborated to describe, with a global approach, the parenting practices just as they are experienced and perceived by the own children. In a sample of 276 students from the 2do to the 6to degree of primary of a private school, the cluster analysis applied confirmed the internal structure of the inventory. On the other hand, the gender of the students as much as the school degree explained little variance in the differences in scores. These differences were, in general, not significant. On the other hand, regarding the psychometric propierties, (1) the analysis supported the validity of the assumed bi-dimensional structure; and (2) the reliability is acceptable.